Medical Liability in the First Period of Independence of Latvia (1918–1940) - Lytvynenko, Anatoliy (Teisė, 2022)
The aim of the paper is to investigate the development of medical law and jurisprudence in the Republic of Latvia during its First Period of Independence (1918–1940), with a particular focus on the liability of doctors for instances of negligence that occurred during the fulfillment of their professional duties. The author seeks to identify the main routes of the emergence of medical liability in the Republic of Latvia, the influence of the laws and legal precedents on the adoption of national legislation relating to medical liability, and the development of case law relating to medical malpractice by Latvian courts during the First Period of Independence.
Keywords: medical malpractice; criminal law; Latvian law; medical law; First Independence of Latvia